Analisis Kelayakan Finansial Dan Non Finansial Usaha Pengolahan Pangan Lokal Di Kabupaten Boyolali - Dewi, Insania Cahyawati; Sarwono, Aris Eddy; Widanti, Yannie Asrie (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
A business feasibility study is crucial to determine the viability of a business and avoid business failure. This study aims to assess the feasibility of Micro, Small, and Medium Enterprises (MSMEs) in Boyolali Regency engaged in food processing, namely processed cow milk products, chips, and herbal medicine. Data collection used interviews with business owners and direct observation of the business premises. This study uses a qualitative approach to analyze non-financial aspects, such as product marketing and legal aspects related to business permits from the data collected. In contrast, quantitative methods are used to analyze financial aspects measured using the Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR) methods. The results of this study indicate that the marketing aspect of local food processing businesses in the form of processed cow milk, chips, and herbal medicine in Boyolali Regency has promising business prospects due to the high market demand every month and the achievement of predetermined market targets, in the legal aspect it also shows that the business already has an NIB from the government and also supports other permits such as halal certificates and P-IRT, making it easier to manage other permits and develop marketing. When viewed from the financial aspect, the business can be declared feasible because based on the Net Present Value (NPV) at Nani's Ice Cream of Rp 436,821,441.64 while NN Kriuk is Rp 397,908,137.49 and Jamu Nyah Rudi is Rp 265,057,461.54. The Internal Rate of Return (IRR) results for Nani's Ice Cream are 70.3%, NN Kriuk 57.4%, and Jamu Nyah Rudi 42.3%. So, this research can help owners develop broader marketing strategies and identify risk management.